2021
DOI: 10.1126/sciadv.abc2931
|View full text |Cite
|
Sign up to set email alerts
|

Lowering apolipoprotein CIII protects against high-fat diet–induced metabolic derangements

Abstract: Increased levels of apolipoprotein CIII (apoCIII), a key regulator of lipid metabolism, result in obesity-related metabolic derangements. We investigated mechanistically whether lowering or preventing high-fat diet (HFD)–induced increase in apoCIII protects against the detrimental metabolic consequences. Mice, first fed HFD for 10 weeks and thereafter also given an antisense (ASO) to lower apoCIII, already showed reduced levels of apoCIII and metabolic improvements after 4 weeks, despite maintained obesity. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 50 publications
4
24
0
Order By: Relevance
“…Lipolysis is inhibited by insulin and stimulated by catecholamines, and functional studies in isolated adipocytes from SAT and VAT, from all experimental groups, revealed that lowering apoCIII normalizes these responses. This clearly shows that there is a restored insulin sensitivity in WAT, as previously shown in liver and BAT, which is a key factor for an efficient glucose and lipid metabolism [9].…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Lipolysis is inhibited by insulin and stimulated by catecholamines, and functional studies in isolated adipocytes from SAT and VAT, from all experimental groups, revealed that lowering apoCIII normalizes these responses. This clearly shows that there is a restored insulin sensitivity in WAT, as previously shown in liver and BAT, which is a key factor for an efficient glucose and lipid metabolism [9].…”
Section: Discussionsupporting
confidence: 79%
“…Hypertriglyceridemia often occurs in obesity and there is a positive correlation between apolipoprotein CIII (apoCIII) and triglycerides [ 4 , 5 , 6 ]. In recent years apoCIII has become interesting as a co-actor in the development of overweight and insulin resistance [ 7 , 8 , 9 ]. During conditions of insulin resistance, there is a parallel increase in intra-islet apoCIII associated with local islet inflammation and β-cell dysfunction/apoptosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations